A Analisis Pengaruh Kebijakan Stimulus Pemerintah Terhadap Meningkatnya Penjualan Mobil Pada Masa Pandemi Covid-19 - Zahran Alwi; Muhammad Yafiz (Al-Buhuts, 2022)
The purpose of this research is to examine the impact of government stimulus initiatives on increasing car sales during the Covid-19 pandemic. The research method used is a qualitative method with an analytic descriptive approach. The results of the study prove that PPnBM incentives have a beneficial effect on car sales, with a significant difference between car sales before and after the incentives. This illustrates the company's effectiveness in using government programs to boost car sales, one of which is the PPnBM incentive policy for recent car sales.